Strategi Implementasi Pendidikan Karakter di Masa Pandemi Covid-19; Studi Kasus di MAN 2 Banyuwangi - Rasmuin Rasmuin; Saidatul Ilmi (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
All this time, character education can be done well through offline learning in schools. Teachers can control student activities in school directly during learning. The problem arose when Covid-19 began to plague which required offline learning to be eliminated and replaced with online learning. This study aims to reveal how the strategy of MAN 2 Banyuwangi as one of the favorite schools in implementing character education in the Covid-19 pandemic era. Data collection was carried out through observation where the researcher went directly to the field to observe the learning process. Data collection was also carried out through interviews with related parties, as well as documentation obtained from learning activities during the pandemic. The data were then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. From this research, it can be concluded that in carrying out character education during the Covid-19 pandemic there are at least three main things done by the school. First, forming a distance learning atmosphere is exactly the same as studying in school. Second, be consistent in implementing the school culture that is usually done in schools and still adapting to existing conditions. Third, establish solid cooperation between schools and parents.